Transcriptome analysis of the circadian clock gene BMAL1 deletion with opposite carcinogenic effects - Emisoglu-Kulahli, Handan; Gul, Seref; Morgil, Hande; Ozcan, Onur; Aygenli, Fatih; Selvi, Saba; Kavakli, Ibrahim Halil (Springer Heidelberg, 2021)
We have previously reported that the deletion of BMAL1 gene has opposite effects in respect to its contribution to the pathways that are effective in the multistage carcinogenesis process. BMAL1 deletion sensitized nearly normal breast epithelial (MCF10A) and invasive breast cancer cells (MDA-MB-231) to cisplatin- and doxorubicin-induced apoptosis, while this deletion also aggravated the invasive potential of MDA-MB-231 cells. However, the mechanistic relationship of the seemingly opposite contribution of BMAL1 deletion to carcinogenesis process is not known at genome-wide level. In this study, an RNA-seq approach was taken to uncover the differentially expressed genes (DEGs) and pathways after treating BMAL1 knockout (KO) or wild-type (WT) MDA-MB-231 cells with cisplatin and doxorubicin to initiate apoptosis. Gene set enrichment analysis with the DEGs demonstrated that enrichment in multiple genes/pathways contributes to sensitization to cisplatin- or doxorubicin-induced apoptosis in BMAL1-dependent manner. Additionally, our DEG analysis suggested that non-coding transcript RNA (such as lncRNA and processed pseudogenes) may have role in cisplatin- or doxorubicin-induced apoptosis. Protein-protein interaction network obtained from common DEGs in cisplatin and doxorubicin treatments revealed that GSK3 beta, NACC1, and EGFR are the principal genes regulating the response of the KO cells. Moreover, the analysis of DEGs among untreated BMAL1 KO and WT cells revealed that epithelial-mesenchymal transition genes are up-regulated in KO cells. As a negative control, we have also analyzed the DEGs following treatment with an endoplasmic reticulum (ER) stress-inducing agent, tunicamycin, which was affected by BMAL1 deletion minimally. Collectively, the present study suggests that BMAL1 regulates many genes/pathways of which the alteration in BMAL1 KO cells may shed light on pleotropic phenotype observed.
Keywords: BMAL1; Circadian clock; Apoptosis; Cancer; RNA-seq; Transcriptome